2002
DOI: 10.1046/j.1341-8076.2002.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal oral hydration on amniotic fluid index in women with pregnancy‐induced hypertension

Abstract: Pregnancy-induced hypertension adversely affects the increase in amniotic fluid volume with maternal hydration. This observation is of clinical relevance in the management of oligohydramnios associated with pregnancy-induced hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Simple and long-term maternal hydration with oral water or intravenous hypotonic fluid appeared to increase amniotic fluid volume and seemed to be beneficial in the preventing and managing oligohydramnios during labor (category IIa evidence) [17,18]. In pregnancyinduced hypertensive gravidae, the effect on amniotic fluid index was not as pronounced as in normotensive gravidae (category IIa evidence) [19].…”
Section: Acute Systemic Mild Dehydration or Hypohydrationmentioning
confidence: 97%
“…Simple and long-term maternal hydration with oral water or intravenous hypotonic fluid appeared to increase amniotic fluid volume and seemed to be beneficial in the preventing and managing oligohydramnios during labor (category IIa evidence) [17,18]. In pregnancyinduced hypertensive gravidae, the effect on amniotic fluid index was not as pronounced as in normotensive gravidae (category IIa evidence) [19].…”
Section: Acute Systemic Mild Dehydration or Hypohydrationmentioning
confidence: 97%
“…The condition may be responsible for fetal malpresentation, umbilical cord compression, meconium staining, increased prenatal mortality and morbidity, and increased operative delivery. [3][4][5] Some conditions, such as renal agenesis, post-term labor and pregnancy induced hypertension, 6 can result in oligohydramnios. Some treatments are available or are under evaluation for oligohydramnios, including intravenous hydration, 7-9 1-deamino [8-D-arginine] vasopressin administration, 10 and amnion infusion during labor, which, although effective is an invasive method and can only be performed during labor when the membranes have ruptured and must be kept under intensive observation for a long period.…”
Section: Introductionmentioning
confidence: 99%
“…Significant improvement in amniotic fluid volume after maternal oral hydration has also been shown in pregnancies with oligohydramnios [13][14][15] .…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies had already shown an increase in amniotic fluid volume after acute maternal oral hydration both in normal pregnancies [14,17] , as well as those with oligohydramnios [18,19] . It remains to be verified if the same response is observed in pregnancies with fetal gastroschisis and oligohydramnios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation